The Effect of Regional Original Revenue, Transfer Revenue, and Regional Expenditure on Regional Government Financial Performance (A Study of Regencies and Cities in The Province of Bali, 2019–2023) - Ni Nyoman Wirastiyanti Paulina; Ni Luh Supadmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The implementation of regional autonomy in Indonesia aims to reduce regional dependence on the central government. In this context, local governments are expected to enhance their own-source revenue sources. In reality, not all regions are capable of becoming fully independent. The dependency of regencies and cities in Bali Province indicates that local governments have not yet optimized their regional potential to increase Regional Original Revenue (PAD). This dependency affects their fiscal independence and overall financial performance. This study aims to empirically examine the effect of PAD, transfer revenue, and regional expenditure on financial performance from the perspective of agency theory. The study was conducted across all regencies and cities in Bali Province, using secondary data sourced from the budget realization reports obtained from each local Financial and Asset Management Agency (BPKAD). The study included 9 regencies/cities with 45 observations. A census sampling method was applied, where the entire population was used as the sample. The data were analyzed using multiple linear regression. The results show that PAD and transfer revenue have a positive effect on financial performance, while regional expenditure has a negative effect. It is recommended that local governments in Bali optimize their PAD by strengthening the tax sector, service charges, and asset management to improve fiscal independence.